Analisis Resepsi Tentang Konten Pornografi Pada Kanal Youtube Frontal Tv - Hendrayana Saputra; Suhendra Atmaja; Nur’aeni Nur’aeni (JIKA (Jurnal Ilmu Komunikasi Andalan), 2022)
Youtube is one of the new media products that has a big impact on every individual. The internet is used as a supporting instrument for Youtube to spread its products. The Frontal TV Youtube channel is a growing channel that creates and presents pornographic content, because pornography has bad effects that can persuade various groups of people, so researchers need to know the meaning of audiences regarding pornographic content through several informants. This study borrows the reception theory of Stuart Hall's model and the concepts of encoding and decoding theory. The research method uses a descriptive qualitative approach, data collection methods in the form of observation, in-depth interviews, literature study, and documentation, as well as the Stuart Hall reception analysis method to dissect the data. The results of research conducted on three research informants named Ivan Argeswara, Faradhita Azhari, and Helmi Yudahshetia.